Tumor-associated fibroblasts derived exosomes induce the proliferation and cisplatin resistance in esophageal squamous cell carcinoma cells through RIG-I/IFN-β signaling. Issue 5 (2nd May 2022) - Cui, Yayun; Zhang, Shu; Hu, Xiaohan; Gao, Fei
ABSTRACT: Esophageal squamous cell carcinoma (ESCC) is a common type of malignant cancer. There is growing evidence suggesting that exosomes may participate in the cellular communication of tumor-associated fibroblasts (TAFs). However, the cisplatin resistance of TAF-derived exosomes to ESCC cells remains to be further studied. Exosomes were isolated from TAFs and characterized with Western blot and TEM assays. ESCC cell lines (TE-1 and KYSE-150) were incubated with TAFs-derived exosomes. To explore the biological function of TAF-derived exosomes in ESCC cell proliferation, apoptosis, and chemosensitivity, we conducted MTT assays and Flow Cytometry. The effects in vivo were also verified via Xenograft mice models. We found that TAFs-derived exosomes led to enhanced cell proliferation and reduced apoptosis of cells, accompanied by increased expression of RIG-I/IFN-β, and TAFs derived exosomes may affect the chemosensitivity to cisplatin via RIG-I/IFN-β signaling in ESCC. Taken together, ESCC cells could communicate with TAFs cells via TAFs-derived exosomes. Our findings might represent a novel mechanism involved in ESCC and may provide a potential biomarker for ESCC. GRAPHICAL ABSTRACT: uf0001